Epidemiology and pharmacological effects of cannabis use - Ün, Burçin (Journal of Dependence, 2025)
Cannabis (marijuana) is a widely consumed and frequently abused substance worldwide. Shortly after being ingested, the tetrahydrocannabinol (THC) contained within it is known to cause effects such as euphoria, relaxation, and alterations in perception. Cannabis use and the accompanying problems are rapidly increasing globally and in our country. This situation creates serious problems in social, economic, and health domains. Cannabis addiction not only reduces individuals’ quality of life but also damages family structures and negatively impacts the overall welfare of society. Economically, the efforts and treatment processes to combat cannabis use incur significant costs and result in loss of workforce productivity. Health-wise, it leads to various physical and psychological problems. Preventing cannabis use is crucial for the welfare of our country and the health of our future generations. Therefore, it is necessary to have a thorough understanding of cannabis, its pharmacological properties, and the effects it causes in users. This review provides general information on cannabis use, its pharmacological properties, and its effects on users. It is believed that this information can make significant contributions to academic studies aimed at protecting public health and reducing cannabis use